Are gender-science stereotypes barriers for women in science, technology, engineering, and mathematics? Exploring when, how, and to whom in an experimentally-controlled setting - Sebastián-Tirado, Alba; Félix-Esbrí, Sonia; Forn, Cristina; Sanchis-Segura, Carla (Frontiers in Psychology, 2023)
Based on Social Cognitive Career Theory principles, the present study sought to investigate whether stereotype threat experiences could act as a barrier and reduce the persistence of women in mathintensive activities. More specifically, we assessed whether the experimental activation of stereotypes about women's lower math capabilities affected the performance, persistence, and self-selected difficulty of engineering students in a math task which required sustained effort. We also evaluated the relationships between these effects and the participants' pre-testing gender-science stereotypes and math self-concept. A sample of 340 engineering students (175 and 165 self-identified as males and females, respectively) were recruited and randomly assigned to a control (Con) or stereotype threat (StA) condition to form four similarly sized groups. All participants rated their self-concept in four academic domains (math, chemistry, physics, and coding), completed the gender-science Implicit Association Test, and a "reading comprehension task" that served to promote the stereotype threat manipulation immediately before facing a modified version of the Math Effort Task (M-MET). We observed that, in the control condition, M-MET performance, self-selected difficulty, and persistence were similar in female and male participants, independent of their gender-science implicit stereotypes but correlated to their math self-concept scores. In contrast, the StA condition triggered opposite effects in female and male students, so they showed decreased/enhanced M-MET performance and self-selected difficulty, respectively. This experimental condition also resulted in enhanced persistence of the male students without affecting the number of trials completed by female students. These effects were correlated with the strength of the participants' gender-science implicit stereotypes but not with their math self-concept scores. In fact, as revealed by finer-grain analyses, stereotype threat only had a significant impact on individuals harboring stereotypical gender-science implicit associations. Therefore, it is concluded that: 1) stereotypes can promote differences between male and female engineering students in their performance, self-confidence, and persistence in math-related activities; 2) These effects seem to be more prominent in individuals implicitly perceiving science as a masculine domain.The relevance of these findings to explain women's enhanced abandonment rates of math-intensive studies is discussed.